Environmental neurodevelopment toxicity from the perspective of Bronfenbrenner's bioecological model: a case study of toxic metals - Homègnon Antonin Ferréol Bah; Nathália Ribeiro dos Santos; Daisy Oliveira Costa; Chrissie Ferreira de Carvalho; Victor Otero Martinez; Erival Amorim Gomes-Júnior; José Antônio Menezes-Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
A growing body of literature reports the need for an integrated approach to study the effects of the physical environment on the neurodevelopment of children. Assessment of the true neurotoxicity of pollutants cannot be performed separately from the ecological and multidimensional contexts in which they act. In this study, from the perspective of the Bronfenbrenner's bioecological model, a conceptual model was developed that encompasses the social and biological characteristics of children from the gestational period to childhood, considering exposure to toxic metals. First, we present the toxicity of the main metals and some concept notions that we used in our framework, such as social and structural determinants of health, allostatic load, embodiment, and epigenetic concepts. Then, the main aspects of the Bronfenbrenner's bioecological model, which allow integration of the gene-social relationship in addition to the physical environment, where these metals act, are explained. Finally, we present and discuss the conceptual framework showing how, in real life, biological and social factors may together influence the neurodevelopment of children. Although this model is based on a group of contaminants, it opens new horizons on how environmental sciences, such as neurotoxicology and environmental epidemiology, can articulate with the theoretical models from human sciences to provide a broader approach to study the effects on human neurodevelopment.